PENGARUH FAKTOR-FAKTOR PERILAKU INDIVIDUAL TERHADAP PERILAKU ETIS KARYAWAN DI PT. MULTI KARYA CITRA MANDIRI KABUPATEN BOJONEGORO - jurnalmap map; Wawan Gunawan; Woro Utari (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2019)
ABSTRACT The purpose of this study is to describe and analyze both simultaneously dan partially effect on individual behavioral factors consisting of emotional intelligence, spiritual intelligence, locus of control, equity sensitivity and ethical behavior. This research type is explanatory research that is research which explain the influence of independent variable to dependent variable and questionnaire as the main data collection tool. Population in this research is all of employees of PT. Multi Karya Citra Mandiri of Bojonegoro which amounted to 480 people. Sampling technique using purposive sampling taken from employees with staff level, staff level was taken because the staff have experience, working period and higher education level than the operator. The sample of this study were 30 people who subsequently made as respondents. The results showed that the variable of emotional intelligence, spiritual intelligence, locus of control, equity sensity have significant effect simultaneously to ethical behavior. Variables of emotional intelligence, spiritual intelligence and locus of control partially have a significant influence on ethical behavior of PT. Multi Karya Citra Mandiri of Bojonegoro. The equity variable of sensityvity partially has no significant effect on ethical behavior. Keywords: emotional intelligence, spirituali, equity sensity, ethical behavior